1993
DOI: 10.3109/14015439309101356
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effectiveness of voice therapy with a male-to-female transsexual subject

Abstract: Tuomi, S. K. (1993). Evaluation of the effectiveness of voice therapy with a male-to-female transsexual subject. Scand J Log Phon, 18: 105-109.The benefits of voice therapy with a 44-year-old male-to-female transsexual subject were investigated. Voice therapy was aimed at increasing the subject's fundamental trequcncy to approximatc that of a female's. Spectrographic analysis revealed that the subject's average fundamental frequency increased from 100.7 Hz to 135.4 Hz.Perceptual analysis of the subject's voice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Early clinical research reported single subject case studies (Bralley, Bull, Gore, & Edgerton, 1978;Hooper, 1985;Kalra, 1977;Kaye, Bortz, & Toumi, 1993;Mount & Salmon, 1988;Yardley, 1976); more recently small group studies have reported outcomes of speech therapy (Byrne et al, 2003;Dacakis, 2000;Neumann et al, 2002b;Soderpalm et al, 2004) and pitch-elevating surgery (Brown, Perry, Cheesman, & Pring, 2000;de Jong, 2003;Gross, 1999;Kunachak, Prakunhungsit, & Sujjalak, 2000;Neumann et al, 2002b;Wagner, Fugain, Monneron-Girard, Cordier, & Chabolle, 2003;Yang et al, 2002). However, further research is needed to evaluate specific techniques and protocols.…”
Section: Evidence-based Practice In Transgender Speech and Voice Changementioning
confidence: 91%
See 2 more Smart Citations
“…Early clinical research reported single subject case studies (Bralley, Bull, Gore, & Edgerton, 1978;Hooper, 1985;Kalra, 1977;Kaye, Bortz, & Toumi, 1993;Mount & Salmon, 1988;Yardley, 1976); more recently small group studies have reported outcomes of speech therapy (Byrne et al, 2003;Dacakis, 2000;Neumann et al, 2002b;Soderpalm et al, 2004) and pitch-elevating surgery (Brown, Perry, Cheesman, & Pring, 2000;de Jong, 2003;Gross, 1999;Kunachak, Prakunhungsit, & Sujjalak, 2000;Neumann et al, 2002b;Wagner, Fugain, Monneron-Girard, Cordier, & Chabolle, 2003;Yang et al, 2002). However, further research is needed to evaluate specific techniques and protocols.…”
Section: Evidence-based Practice In Transgender Speech and Voice Changementioning
confidence: 91%
“…Thoroughly assessing the client's speech gives a baseline against which to measure change and provides information about which changes would be most useful (Andrews & Schmidt, 1997;Kaye et al, 1993;King et al, 1999). While voice parameters such as fundamental frequency and speaking frequency range can be measured objectively, many speech characteristics associated with gender, such as melody and vocal timbre, cannot be objectively quantified.…”
Section: Evaluating Current Speech Parameters Associated With Gendermentioning
confidence: 98%
See 1 more Smart Citation
“…[2][3][4] Quite understandably then, raising pitch level is one of the primary goals of the voice training in male-to-female transsexuals. [5][6][7][8] Pitch level is not the only characteristic, however, that distinguishes a female from a male voice. Other vocal aspects that have been found to be different in males and females include pitch range and intonation, vocal intensity, resonance, and also vocal quality.…”
Section: Introductionmentioning
confidence: 99%
“…1, 2012 are clear that increasing F 0 alone is generally not sufficient to result in a passing female voice. 10,39,41 However, increasing F 0 is part of the adjustment that seems necessary for many, and a gender-ambiguous F 0 of 150-160 Hz is often targeted. 14,38 In the current investigation, the MFT participants who were consistently perceived as female had a mean F 0 well above the gender-ambiguous range in both the vowel and Rainbow Passage productions.…”
Section: Listener Identification Of Mft Speaker Gendermentioning
confidence: 99%